2018
DOI: 10.1016/s1473-3099(17)30485-1
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for control of antimicrobial resistance

Abstract: Antimicrobial resistance poses a growing threat to public health and the provision of health care. Its surveillance should provide up-to-date and relevant information to monitor the appropriateness of therapy guidelines, antibiotic formulary, antibiotic stewardship programmes, public health interventions, infection control policies, and antimicrobial development. In Europe, although the European Antimicrobial Resistance Surveillance Network provides annual reports on monitored resistant bacteria, national surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
201
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 275 publications
(208 citation statements)
references
References 14 publications
3
201
0
4
Order By: Relevance
“…A previous meta-analysis involving 3,627 participants demonstrated that prior antibiotic use such as carbapenem and aminoglycoside was an important risk factor of carbapenemresistant Klebsiella pneumoniae infection (Liu et al, 2018). Given that roughly 30%-50% of the antibiotic use in hospitals is unnecessary and the limitation of antimicrobial drugs has the potential to reduce the prevalence of CRE, strong antibiotic stewardship policies are urgently needed to curb unnecessary prescribing to ensure more judicious use of antibiotics (Yong et al, 2010;Fleming-Dutra et al, 2016;Tacconelli et al, 2018). Our meta-analysis is in accord with a previous in vitro study which observed that adding a third antibiotic did not enhance synergistic effect in multidrug-resistant Klebsiella pneumonia isolates (Stein et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A previous meta-analysis involving 3,627 participants demonstrated that prior antibiotic use such as carbapenem and aminoglycoside was an important risk factor of carbapenemresistant Klebsiella pneumoniae infection (Liu et al, 2018). Given that roughly 30%-50% of the antibiotic use in hospitals is unnecessary and the limitation of antimicrobial drugs has the potential to reduce the prevalence of CRE, strong antibiotic stewardship policies are urgently needed to curb unnecessary prescribing to ensure more judicious use of antibiotics (Yong et al, 2010;Fleming-Dutra et al, 2016;Tacconelli et al, 2018). Our meta-analysis is in accord with a previous in vitro study which observed that adding a third antibiotic did not enhance synergistic effect in multidrug-resistant Klebsiella pneumonia isolates (Stein et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Rank I was maintained at a significantly low abundance in FMT donors with no antibiotic consumptions. These observations suggested that Rank I could strongly and rapidly respond to clinical antibiotics 56 and was effectively controlled by current policy in developed countries 54 (such as therapy guidelines, antibiotic formularies, antibiotic stewardship programmes, and public health interventions 58 ). However, we found that Rank II was not directly correlated with the clinical antibiotics and was not observed to be effectively controlled in industrialized countries.…”
Section: Discussionmentioning
confidence: 99%
“…1). Based on a review of related literature [24,28], the following criteria were determined to be relevant for the current use case: number of annual cases (as reported globally and positivity rates reported by Prasad et al); case fatality rate; morbidity using disease-adjusted life-years [29]; and impact on treatment decisions (measured from high to low depending on treatment available for a specific pathogen and the diagnostic potential to reduce complications and/or death). Each criterion had defined sub-criteria, as presented in Fig.…”
Section: Priority Profiling Pairwise Comparison and Rankingmentioning
confidence: 99%